Double antibody sandwich enzyme linked Immununosorbent assay kit. - Universiti Putra Malaysia, Research Management Centre (Research Management Centre, Universiti Putra Malaysia, 2005)
Infectious bursal disease (IBD) is one of the mort threathening and highly contagious viral diseases in chickens in the country causing significant economic losses, estimated more than 72 million per year due to high mortality and immunosuppression. IBD outbreak due to veryvirulent IBD virus (wIBDV) was first reported in Malaysia in 1991. Since then the disease continues to occur despite of vaccination against the disease. IBD can only be controlled and prevented by proper biosecurity and vaccination programmes. Recently, we have successfully developed a highly specific and sensitive Double Antibody Sandwich (DAS) Enzyme linked Immunosorbent Assay (ELISA) Kit for the detection of both the antigen (IBD virus) and antibody against IBD. The kit was developed using local isolate of wIBDV (UPM 971302). The ELISA plate was coated with purified rabbit hyperimmune serum (1gG) prepared in New Zealand White rabbits using the purified virus.